Prognostic significance of paraproteinaemia in rheumatoid arthritis. Issue 5 (May 1991) - Kelly, C; Baird, G; Foster, H; Hosker, H; Griffiths, I
Abstract : The incidence of lymphoma and myeloma is increased in rheumatoid arthritis (RA), though the reasons for this are incompletely understood. The predictive value of monoclonal gammopathy in RA for the later development of lymphoproliferative malignancy was assessed. A serum paraprotein was discovered in 23 patients (14 female) with a median age of 58 years and a median duration of RA of six years. The paraprotein was quantified and further investigations, including a bone marrow examination and skeletal survey, were undertaken to study the possible development of a lymphoproliferative disorder. Secondary Sjögren's syndrome was noted in 12 patients. The paraprotein was monoclonal in 21 patients and was classed as IgG (12 cases), IgA (six cases), or IgM (three cases). Biclonal paraproteins were seen in two patients. Free light chains were found in the urine of eight patients. Bone marrow abnormalities were found in 13 subjects. The bone marrow was abnormal in four of six patients with an IgA paraprotein, in two of three with an IgM paraprotein but in only five of 12 patients with an IgG paraprotein. Patients were followed up for a median of four years, and five patients with an abnormal bone marrow developed myeloma, of whom three had an IgA lambda paraprotein. Two other patients developed non-Hodgkin's lymphoma. Extra-articular bone erosions were seen in four patients, three of whom developed myeloma, but the presence of urinary free light chains was not specific for the development of malignancy. Paraproteinaemia in RA indicates monoclonal B cell proliferation and carries a high risk of malignant transformation.